Heterogeneous effects of eccentric training and nordic hamstring exercise on the biceps femoris fascicle length based on ultrasound assessment and extrapolation methods: A systematic review of randomised controlled trials with meta-analyses - Yagiz, G.; Akaras, E.; Kubis, H.-P.; Owen, J. A. (PLOS ONE, 2021)
Objective: To systematically review the effects of eccentric training based on biceps femoris fascicle length using ultrasound assessment and extrapolation methods. Design: Systematic review and meta-analysis of randomised controlled trials. Data sources: CENTRAL, CINAHL Plus with full text, PubMed and OpenGrey databases were searched on 6 July 2021. Eligibility criteria for selecting studies: Randomised controlled trials (RCTs) lasting at least four weeks and presenting data about biceps femoris (BF) fascicle length (FL) as an outcome. Method: Searching databases, screening studies, performing risk of bias assessments and determining the level of evidence (LoE) for each meta-analysis were applied during the study. PRISMA 2020 statement and Cochrane Handbook for Systematic Reviews of Interventions were used as the guidelines of this systematic review. Results: Eight randomised controlled trials included in meta-analyses. Based on the very low and low LoE, eccentric training has small (g = 0.29, 95% CI [-0.26, 0.85]), moderate (g = 0.72, 95% CI [0.17, 1.28]) and large (g = 2.20, 95% CI [0.99, 3.41]) effect sizes (ES) based on manual linear extrapolation (MLE), panoramic ultrasound scanning and trigonometric equation methods, respectively. Similarly, Nordic hamstring exercise (NHE) has small (g = 0.23 [-1.02, 1.47]), small (g = 0.38, 95% CI [-0.50, 1.27]) and large (g = 1.98, 95% CI [0.52, 3.44]) ES based on the MLE, panoramic ultrasound scanning and trigonometric equation methods, respectively. Conclusion: ES of eccentric training, including NHE, vary between the MLE, panoramic ultrasound scanning, and equation methods. The relevant scientific community should have a consensus on measurement standards of the BF FL measurements. Further studies can be conducted to compare the effects of eccentric training based on the ultrasound assessment and extrapolation methods.